Direct Predictive Speed Control of Salient PMSM Drives in Constant Torque and Constant Power Regimes for Electric Vehicles Applications - Mwasilu, Francis (Tanzania Journal of Engineering and Technology, 2021)
A direct speed control of salient permanent magnet synchronous motor (PMSM) drives in constant torque and constant power regimes for electric vehicles applications is presented. The proposed speed control scheme is derived from model predictive control approach where both rotor speed and stator current are formulated in a single objective function that is periodically computed to attain the PMSM drive optimum switching states. The dynamic model of the PMSM intrinsically encompasses the unknown disturbance, which should be rejected for high-performance speed control especially in transient conditions. Consequently, the extended modified augmented state Kalman filter (ASKF) is incorporated in the proposed scheme to enhance the transient performance of the salient PMSM drive. Finally, the proposed speed control strategy reveals a fast-transient speed response when compared to the conventional dual current loop PI-based speed controller over extended speed range and load torque variations. The computer simulation conducted using MATLAB/Simulink and experimental results obtained using PMSM laboratory prototype are presented considering constant torque and constant power regions to confirm the efficacy of the proposed speed control strategy. Keywords: Augmented state Kalman filter (ASKF); electric vehicles (EVs); Constant power regime; permanent magnet synchronous motor (PMSM); predictive speed control.